Risk of Infective Endocarditis Following Invasive Dental Procedures: A Systematic Review and Meta-Analysis - Zhumakyz Kussainova; Mukhit Kulmaganbetov; Askar Abiltayev; Tolkyn Bulegenov; Islam Salikhanov (Public Health Reviews)
ObjectivesThis systematic review and meta-analysis aimed to synthesize evidence and determine the association between IE and dental procedures, including invasive and non-invasive procedures.MethodsWe conducted a systematic search of PubMed, Google Scholar, and Cochrane databases for studies involving procedures such as tooth extraction, scaling, endodontic treatment, oral surgery, and periodontal treatment involving individuals aged ≥15 years. The primary outcome was the incidence of IE following these procedures.ResultsAn association was found between IE and invasive dental procedures (OR 1.49, 95% CI 1.25–1.76; p < 0.00001). Subgroup analysis showed an increased risk of IE following tooth extraction (OR 2.73, 95% CI 1.46–5.11; p = 0.002) and oral surgery (OR 6.33, 95% CI 2.43–16.49; p = 0.0002) in high-risk patients.ConclusionOur study found a strong association between invasive dental procedures and increased IE risk, particularly for tooth extraction and oral surgery in high-risk individuals.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023488546, Identifier CRD42023488546.